The Role of Race and Economic Characteristics in the Presentation and Survival of Patients With Surgically Resected Non-Small Cell Lung Cancer - Varlotto, John M.; McKie, Kerri; Voland, Rickie P.; Flickinger, John C.; DeCamp, Malcolm M.; Maddox, Debra; Rava, Paul Stephen; Fitzgerald, Thomas J.; Walsh, William; Oliveira, Paulo; Rassaei, Negar; Baima, Jennifer; et al. (Frontiers in Oncology, 2018)
Background: Little is understood regarding the inter-relation between economic, marital, and racial/ethnic differences in presentation and survival of surgically-resected lung cancer patients. Our investigation will assess these differences in addition to known therapeutic, patient, and histopathologic factors. Methods: A retrospective review of the SEER database was conducted through the years 2007-2012.The population was split into 9 different ethnic groups. Population differences were assessed via chi-square testing. Multivariable analysis(MVA) were used to detect overall survival(OS) differences in the total surgical population (TS, N = 35,689) in an early-stage (T1-T2 < 4cm N0) surgically-resectable population(ESR, N= 17,931). Lung cancer specific survival (LCSS) was assessed in the ESR. Results: In the TS population, as compared to Whites, Blacks and Hispanics presented with younger age, more adenocarcinomas, lower rates of marriage, lower rates of insurance, less stage I tumors, and had less nodes examined, but their type of surgical procedures and OS/LCSS were the same. MVA demonstrated that lower OS and LCSS were associated with males, single/divorced/widowed partnership, lower income(TS only), and Medicaid insurance. MVA also found that Blacks and Hispanics had a similar OS/LCSS to Whites and that all ethnic groups were associated with a similar or better outcomes. 90-day mortality and positive nodes were correlated with not having insurance and not being married, but they were not associated with ethnicity. Conclusions: In TS and ESR groups, OS was not different in the two largest ethnic groups (Black, Hispanic) as compared to Whites, but was related to single/widowed/divorced status, Medicaid insurance, and income (TS group only). Nodal positivity was associated with patients who did not have a married partner or insurance suggesting that these factors may impact disease biology. Economic and psycho-social variables may play a role in survival of early-stage lung cancer in addition to standard histopathologic and treatment variables.